Thermal activation of recycled plaster of Paris at 160°c with silubit G80 additive for enhanced material properties - Hamdan, Ainun Fathiah; Awang, Nor Nazida; Hassan, Oskar Hasdinor (2025)
The increasing demand for environmentally sustainable materials has driven interest in the recycling and reuse of industrial waste, particularly in the ceramics and moulding industries. This study explores the enhancement of Recycled Plaster of Paris (RPOP) by using Silubit G80 as an additive, with the goal to improving its physical properties and achieving characteristics comparable to New Plaster of Paris (NPOP). The aim of this study is to improve the setting time, compressive strength, porosity and absorption of RPOP 160℃ accompanied by the presence of Silubit G80 as additive. The recycling process involves collecting used Plaster of Paris moulds, then crushed, sieved, and drying temperature at 160°C for one hour. This drying process facilitates the partial removal of crystallised water, rendering the material reusable. The processed powder is mixed with water at a ratio of 40:60 (water and material), and Silubit G80 is introduced in incremental concentrations of 0.1%, 0.3%, 0.5%, 1.0%, 1.5%, and 2.0% to evaluate its impact on the material’s performance. The study demonstrates that the addition of Silubit G80 significantly enhances the structural characteristics of RPOP, improving its setting time and reducing both porosity and water absorption. These improvements contribute to making RPOP a viable and sustainable alternative to NPOP. Furthermore, the findings encourage awareness of the potential to recycle and reuse Plaster of Paris, which in turn supports environmental conservation by reducing solid waste generation in the moulding and ceramic industries. Ultimately, this approach facilitates waste reduction and fosters the adoption of sustainable practices in the ceramic and moulding industries.